2016
DOI: 10.1007/s00429-016-1289-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential origin of the activation of dorsal and ventral dentate gyrus granule cells during paradoxical (REM) sleep in the rat

Abstract: We recently demonstrated that granule cells located in the dorsal dentate gyrus (dDG) are activated by neurons located in the lateral supramammillary nucleus (SumL) during paradoxical sleep (PS) hypersomnia. To determine whether these neurons are glutamatergic and/or GABAergic, we combined FOS immunostaining with in situ hybridization of vesicular glutamate transporter 2 (vGLUT2, a marker of glutamatergic neurons) or that of the vesicular GABA transporter (vGAT, a marker of GABAergic neurons) mRNA in rats disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…We finally showed that the lateral supramammillary nucleus (SuML) was the only subcortical structures containing neurons activated during PSR and projecting to the DG. Further, lesion of the SuML induced a disappearance of cFos staining in the dorsal but not the ventral DG 4,5 .…”
mentioning
confidence: 93%
“…We finally showed that the lateral supramammillary nucleus (SuML) was the only subcortical structures containing neurons activated during PSR and projecting to the DG. Further, lesion of the SuML induced a disappearance of cFos staining in the dorsal but not the ventral DG 4,5 .…”
mentioning
confidence: 93%
“…The claustrum (CLA) shares widespread connections with the cortex in a variety of mammalian species (Atlan, Terem, Peretz‐Rivlin, Groysman, & Citri, ;Dinopoulos et al, ;LeVay & Sherk, ; Olson & Graybiel, ; Reser et al, ; Sadowski, Morys, Jakubowska‐sadowska, & Narkiewicz, ; Smith & Alloway, ; Tanné‐Gariepy, Boussaoud, & Rouiller, ; Torgerson, Irimia, Goh, & Van Horn, ; Wang et al, ; White et al, ; Zingg et al, ), and has been postulated to play an important role in processes ranging from attention (Goll, Atlan, & Citri, ; White et al, ) and salience detection (Kim, Matney, Roth, & Brown, ; Remedios, Logothetis, & Kayser, , ) to the coordination of rapid eye movement (REM) sleep (Billwiller, Renouard, Clement, Fort, & Luppi, ; Renouard et al, ; for review see Brown et al, ; Crick & Koch, ; Mathur, ). Progress in determining its precise function and anatomical organization, however, has been hindered by the difficulty in targeting CLA neurons for experimental manipulation due to its small, irregular shape.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that the SuM controls hippocampal theta rhythm (Kocsis and Vertes 1994 ; Vertes and Kocsis 1997 ; Kocsis and Kaminski 2006 ) and is involved in emotional learning and memory (Pasquier and Reinoso-Suarez 1976 ; Richmond et al 1999 ; Pan and McNaughton 2002 ; Santín et al 2003 ; Pan and McNaughton 2004 ; Shahidi et al 2004 ). By combining retrograde tracing, neurotoxic lesion and FOS immunostaining, it was recently shown that SuML GABA/glutamate neurons are responsible for the activation of dDG granule cells during paradoxical sleep (PS) (Renouard et al 2015 ; Billwiller et al 2017 ). Such activation may play a key role in the previously reported beneficial effect of PS on learning and memory (Maquet et al 2000 ).…”
Section: Introductionmentioning
confidence: 99%